Construindo o direito de acesso aos arquivos da repressão: o caso do Departamento de Ordem Política e Social de Minas Gerais - Shirlene Linny da Silva (2007)
This research is about the question of the access to informationconsidering the recent context of Brazilian history marked by thetransition from a military dictator-ship to a democratic system. Theresearch was based on the case study about the access to documents ofthe Departamento de Ordem Política e Social do Estado de MinasGerais (DOPS). Starting from the hypothesis that the process ofaccess to information is a multidimensional phenomenon and havingas main theoretical reference the concept of information regime andthe relative approaches to the access right to information, the case wasanalyzed according to three categories: legal aspects, context ofproduction and use of the documents, and political-social disputes.Out of the categories above, it argued the Brazilian legislation aboutthe access to information and the constitution and operation of theinformation services and political police in Brazil, correlating suchthemes with the access process to DOPS's documents.